Original paperDermoscopy of halo nevus in own observation - Kamińska-Winciorek, Grażyna; Szymszal, Jan (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Introduction : Halo nevus (HN) is a rare dermatologic entity characterized by a typical whitish rim encircling the existing melanocytic nevus resembling a halo. The clinical picture is suggesting its diagnosis, but so far only several dermoscopic descriptions of halo nevus have existed in the PubMed database. Aim : To present the clinical and dermoscopic characteristics of halo nevus observed in dermoscopy. Material and methods : Fifteen patients were diagnosed clinically and dermoscopically with halo nevus during planned routine dermoscopic examinations of all melanocytic lesions in 2007–2013. All digital images stored in the computer database were analyzed retrospectively according to the procedure described in the study. The clinical and dermoscopic parameters such as the dermoscopic pattern, color of nevus, special features and description of the surrounding halo were analyzed statistically. Results: We analyzed 22 halo nevi (9 in females, 13 in males) in 15 patients (7 females, 8 males) diagnosed during the dermoscopic examination. The mean age of patients during dermoscopic examinations was 18.2 years. Mean patients’ age at HN onset was 15.7 years. Halo nevi occurred the most often as a solitary lesion. The ratio of multiple halo nevi to solitary halo nevus was 5 : 10. Every third halo nevus was located on the posterior trunk upper. In 68.2% of HN cases, the surrounding rim (halo) was characterized by its homogenous, whitish color. Conclusions : Dermoscopic patterns such as uniform globular and structureless constituted one-third each of them in all analyzed patterns.